2015
DOI: 10.1177/1708538115586682
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes and factors influencing late survival following elective abdominal aortic aneurysm repair: A 24-year experience

Abstract: Open repair offers a good long-term treatment option for patients with an abdominal aortic aneurysm and in our experience there is no significant difference in late survival between open abdominal aortic aneurysms repair and endovascular repair. Consideration of the factors identified in this study that predict reduced long-term survival for open abdominal aortic aneurysms repair and endovascular repair should be considered when deciding repair of abdominal aortic aneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…They identified age, female sex, American Society of Anesthesiologists class, COPD, peripheral arterial disease, renal impairment, and heart failure as factors associated with late death. 11 This is similar to a review of 247 patients treated with EVAR reported by Lim et al, in which they identified advanced age, renal disease, and oxygen-dependent COPD as predictors of overall mortality. In addition, advanced heart failure (ejection fraction <40%) and current cancer treatment were major predictors.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…They identified age, female sex, American Society of Anesthesiologists class, COPD, peripheral arterial disease, renal impairment, and heart failure as factors associated with late death. 11 This is similar to a review of 247 patients treated with EVAR reported by Lim et al, in which they identified advanced age, renal disease, and oxygen-dependent COPD as predictors of overall mortality. In addition, advanced heart failure (ejection fraction <40%) and current cancer treatment were major predictors.…”
Section: Discussionsupporting
confidence: 86%
“…11 Although our study is limited to overall mortality, they delineated that cardiac, respiratory, and oncologic causes remain the leading causes of death for patients after AAA repair (accounting for two-thirds of late deaths). They identified age, female sex, American Society of Anesthesiologists class, COPD, peripheral arterial disease, renal impairment, and heart failure as factors associated with late death.…”
Section: Discussionmentioning
confidence: 98%
“…Another similar longitudinal study has been reported in 2015 . The objective of this study was to assess predictors of long‐term survival and compared elective open abdominal aortic aneurysm repairs and endovascular repairs as an institutional experience.…”
Section: Discussionmentioning
confidence: 83%
“…The per-protocol analysis hinted at some benefit in patients who actually underwent EVAR. A recent observational study from a single institution in Queensland, Australia, 109 reported no differences in 5-, 10-and 15-year survival rates between OR (n = 982, median follow-up 6.5 years) and EVAR (n = 358, median follow-up 4.0 years), but suffered from incomplete patient reporting. The EUROpean collaborators on Stent-graft Techniques for abdominal aortic Aneurysm Repair (EUROSTAR) database has reported that rate of secondary sac rupture after EVAR is low for the first 4 years, but after this time the rate appears to increase, particularly in those with known sac expansion.…”
Section: Evar Trialmentioning
confidence: 96%